Implementation of Brandt Daroff Exercise in Vertigo Patients at Sawah Lebar Community Health Center, Bengkulu City, 2025 - Yulita, Wanti Marza; Pebriani, Emi; Aprianti, Delta (Multidisciplinary Journals, 2025)
Cases of vertigo at Sawah Lebar Community Health Center increased from 68 in 2022 to 84 in 2024, with pharmacological therapy as the main treatment. Brandt Daroff Exercise is a simple and safe technique proven to reduce headache intensity in vertigo patients. This study aimed to determine its effectiveness in lowering headache pain scales among vertigo patients in the Sawah Lebar Community Health Center, Bengkulu City. The research used a descriptive case study on one 38-year-old patient. The intervention was conducted for 10 consecutive days, three times daily, lasting 20–30 minutes per session. Pain intensity was assessed using the Numeric Rating Scale before and after each session. Results showed a consistent reduction in pain scale from 6 on the first day to 1 on the tenth day, with gradual improvement observed in all daily measurements. The findings indicate that Brandt Daroff Exercise effectively decreases headache levels and supports non-pharmacological management of vertigo. This exercise is easy to perform, cost-effective, and suitable for use in primary healthcare settings. It can also be taught as a home-based self-therapy for patients to improve symptom control and enhance their quality of life.